Levels of Learning Autonomy: A Comparative Study of Freshmen and Seniors at the Faculty of Human Sciences - Alkishir, Ebtissam; Mohsen, Ghada (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study aimed to measure and compare the levels of autonomy between freshmen and seniors at the Faculty of Human Sciences at Alasmarya Islamic University. A quantitative method was employed to assess the difference and significance of autonomy levels. The Learner Autonomy Test, adapted from Dafei (2007), was used for data collection. The results indicated that freshmen exhibited higher autonomy levels than seniors, with 90% confidence. However, this difference may not be significant at stricter significance levels. Further research is needed to explore the reasons behind this difference.